2013
DOI: 10.1016/j.juro.2012.11.150
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Phase 1 Dose Escalation Study of Intravesical TMX-101 in Patients with Nonmuscle Invasive Bladder Cancer

Abstract: Intravesical treatment with TMX-101 is safe. The side effects are common but mild and mostly limited to the genitourinary tract. There is a low systemic uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 31 publications
0
16
0
4
Order By: Relevance
“…[22] Its administration via intravesical instillation has also been found to be safe and tolerable. [23] In the recently completed phase 2 trial involving patients with carcinoma in situ (CIS), 2 out of 12 patients demonstrated negative cytology and biopsy results at 6 weeks following treatment. [24]…”
Section: Bcg-naïvementioning
confidence: 99%
“…[22] Its administration via intravesical instillation has also been found to be safe and tolerable. [23] In the recently completed phase 2 trial involving patients with carcinoma in situ (CIS), 2 out of 12 patients demonstrated negative cytology and biopsy results at 6 weeks following treatment. [24]…”
Section: Bcg-naïvementioning
confidence: 99%
“…139 A multicentre phase 1 study was reported the safeness of TMX-101 (liquid formulation of imiquimod) intravesical administration for NMIBC patients. 140…”
Section: Tlr7 Agonistsmentioning
confidence: 99%
“…45,46 In the clinical setting, TMX-101, a variant formulation of imiquimod, was tested in a phase 1 trial demonstrating safety in 16 patients. 47 A phase 2 trial (NCT01731652) has been developed. 19 …”
Section: Lenalidomidementioning
confidence: 99%